Update on Malaria Diagnostics and Test Utilization - Mathison, Blaine A. (J Clin Microbiol, 2017)
Malaria is a potentially life-threatening disease requiring rapid diagnosis and treatment. Although microscopic examination of thick and thin blood films remains the gold standard for laboratory diagnosis, rapid antigen tests and nucleic acid amplification methods may also play a useful role in detection of acute infection. This review discusses the advantages and disadvantages of the commonly used diagnostic methods and provides important practice points for optimal malaria test utilization.